IMPLEMENTASI MEDIA GURITA BERHITUNG UNTUK MENINGKATKAN KEMAMPUAN NUMERASI PADA ANAK KELOMPOK B USIA 5-6 TAHUN DI RA TUNAS CENDEKIA TULUNGREJO - Nita Riatul Hikmah; Pascalian Hadi Pradana; Wedya Puspita (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Students at RA Tunas Cendekia are low in numeracy skills and are very difficult to condition due to the lack of interesting media in learning, so to solve this problem, it is necessary to develop learning media that are appropriate to the interests and characteristics of students. This is generally done in order to know and understand how to use and function the counting octopus media optimally, especially in the pre-mathematics learning process for group B children (Early Childhood 5-6 Years). The objectives are to know how to implement the use of Counting Octopus media in the numeracy learning process for Group B children at RA Tunas Cendekia Tulungrejo, to know how to use counting octopus media to improve numeracy skills in group B children at RA Tunas Cendekia Tulungrejo, to know and describe the responses of group B children to the use of counting octopus media in numeracy learning activities at RA Tunas Cendekia Tulungrejo. The research method used in this study is qualitative research. This type was chosen because it aims to describe in depth the implementation process of the counting octopus media and how it affects the numeracy skills of early childhood. In qualitative research, the researcher acts as the primary instrument, observing, interviewing, and documenting data from natural situations without manipulation. This research does not focus on statistical measurements, but rather on an in-depth understanding of the phenomena occurring in the field. The output produced from this research is to help and make it easier for children to learn to count.